APPROACHES TO VALUES IN EDUCATION (Authors: M. Belok, O. R. Bontrager, H. C. Oswalt, Mary S. Morris, E. A. Erickson) - Jay, Eric G. (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1968)
M. Belok, O. R. Bontrager, H. C. Oswalt, Mary S. Morris, E. A. Erickson. Approaches to Values in Education. Dubuque, Iowa: Wm. C. Brown, 1966. xi, 322 pp.